(untitled) (Research, Society and Development, 2024)
This study addresses the role of the Endemic Disease Control Agent (DCE) in the Prevention and Control of Dengue in the Municipality of Duque de Caxias (RJ). The aim was to analyze the strategic use of DCEs operating in a specific sector in the municipality of Duque de Caxias (RJ), focusing on dengue prevention and control. Using a descriptive and qualitative methodological approach, based on bibliographic and documentary research and a questionnaire applied to 36 DCEs, the results indicate high engagement of DCEs in training but highlight significant challenges, including a lack of resources, insufficient institutional support, community resistance, and safety risks. A majority of 72.2% of agents report not receiving adequate support for their roles, facing shortages of protective equipment and essential materials. The research identifies gaps in the integration between DCEs and other health professionals, as well as in the perceived effectiveness of current public policies. These findings suggest the need for a reassessment of dengue control strategies, including improvements in working conditions, greater integration within the health system, and more effective policies. The study provides insights for the improvement of public health interventions, although the generalization of results requires caution due to methodological limitations, such as the shift to online questionnaires and the focus on a single sector of the municipality.